Strategising Campaigns On Wildlife Trafficking: A Study On Government Agencies And Nongovernmental Organisations (Ngos) In Malaysia And Thailand - Santhanasamy, Esther (2015)
There are many negative impacts due to wildlife trafficking among which is the extinction of species which in turn would affect the humans as any drastic change to the natural world will impact all on earth. Malaysia is a location for illegal hunting and is a hub for international wildlife trafficking. Many incidents include the involvement of Thailand whereby trafficked animals destined to Thailand pass through Malaysia or in some cases, seizes by Custom officials often occur at the Thai-Malaysia border. Poor public awareness is said to be one of the reasons wildlife trafficking crimes occur therefore creating awareness about wildlife trafficking is vital to help curb the problem. One common method to create awareness is through awareness campaigns and both government agencies and non-governmental organisations (NGOs) deploy this method to reach out to their target audience.